Perancangan dan Implementasi Aplikasi Pemilihan Bahan-Bahan Makanan Untuk Menu Makanan Kafetaria Universitas Advent Indonesia Berbasis Web - Vember Ezer Sihotang; Andrew Fernando Pakpahan (TeIKa, 2020)
Proper selection of food ingredients and quantities is a significant step to serve foods with good taste. When the selection of food ingredients is done inappropriately, the food maker can suffer losses because the ingredients chosen exceed the target for their use. Proper data collection in managing food ingredients is also needed by food makers in large quantities to produce delicious food as well. Universitas Advent Indonesia is a boarding campus which organizes and serves food for students on campus. Food serving for students is managed by the Cafeteria Department. One of the challenges that faced by this department is the collection of food ingredients on each food menu. Because of cooking in large portions, errors in the use of food ingredients are often found. In one meal, the cafeteria manager must prepare food for 1000-1500 servings. Then in one day the cafeteria must prepare food for 3000-4500 servings. Therefore, conducting this research aims at designing an information system that can record incoming materials, available materials and exit materials. This study also aims to make it easier for workers in the selection and data collection at the cafeteria of Universitas Advent Indonesia. The method that used in this study is SDLC (System Development Life Cycle), they are: (1) Analysis of Program requirements (Requirements). (2) Design (System Design). (3) Writing the Program Code (coding). (4) Program Testing (Testing). (5) Program Leading (implementation). Based on the design that has been described, it can be concluded that the system built can improve the performance of Universitas Advent Indonesia employees; the information system that is designed includes the selection of food ingredients as well as monitoring incoming, outgoing and available ingredients. The system built can also store data as desired. The design of this system is web-based, the use of this system will be even better if the design of this system is implemented mobile in the future.